Preparação e caracterização de filmes finos automontados de polieletrólitos/TiO2/CdSe para aplicação na geração de hidrogênio a partir da fotocatálise da água - Faria, Ana Claudia Rangel (My University, 2016)
The self-assembled films (SAF) by physical adsorption, compounds of organic polyelectrolytes and inorganic semiconductor nanoparticles are considered an inexpensive process and non-pollutant deposition that gives films with high molecular organization. The aim of this work was to fabricate and characterize SAF via the layerby- layer technique (LbL) and evaluate the potential application of these systems to produce hydrogen (H2) by water splitting technique by solar radiation. In this work were deposited three different sets of films. The cationic system and the number of deposited layers (40) are common to all three types of SAF. The system was composed by the cationic aqueous solution of polycation polyallylamine hydrochloride (PAH), and colloidal inorganic semiconductor cadmium selenide (CdSe). The anionic systems were comprised of aqueous solutions of organic polyanions poly(acrylic acid) (PAA) and poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT: PSS) and colloidal photoactive semiconductor titanium oxide (TiO2 P25 and TiO2 STS-100). Analysis of SAF by profilometry revealed that the thickness of the self-assembled films are of nanometer order; by diffuse reflectance spectrum observed absorption bands in the near ultraviolet region and the visible region and through the chromatography was given the average H2 production. The system with the highest value of H2 production rate - (PAH + CdSe) / (PEDOT: PSS + TiO2 STS-100) - was optimized at 120 layers. In the evaluation of the contribution of the type semiconductor nanoparticle for the generation of H2 results chromatography indicated that the combination of (CdSe + TiO2 STS-100) promotes an increase of 75% from this generation as compared to SAF only composed by the semiconductor TiO2 STS -100.
Filmes finos automontados (FFA) por adsorção física, compostos por polímeros orgânicos e nanopartículas de semicondutores inorgânicos são considerados um processo barato e não-poluente de deposição, que permite obter filmes com elevada organização molecular. Neste trabalho, o principal objetivo foi produzir e caracterizar FFA, através da técnica camada por camada (LbL), bem como avaliar o potencial de aplicação destes sistemas para a produção de hidrogênio (H2) através da quebra da molécula da água por irradiação solar. Foram depositados três conjuntos diferentes de filmes, onde o sistema catiônico e o número de camadas depositadas (40) foram comuns aos três tipos de FFA. O sistema catiônico foi composto pelas soluções aquosa do policátion hidrocloreto de polialilamina (PAH) e coloidal do semicondutor inorgânico seleneto de cádmio (CdSe). Os sistemas aniônicos foram compostos pelas soluções aquosas do poliânions orgânicos poli(ácido acrílico) (PAA) e poli-(3,4-etilenodioxitiofeno):poli(ácido estirenosulfônico) (PEDOT:PSS) e coloidal do semicondutor fotoativo óxido de titânio (TiO2 P25 e TiO2 STS-100). Análises dos FFA realizadas por perfilometria revelaram que as espessuras dos filmes automontados são da ordem nanométrica. Através do espectro de refletância difusa observou-se bandas de absorção na região do ultravioleta próximo à região do visível e, através da cromatografia, foi determinado a taxa média de produção H2. O sistema com o maior valor da taxa de produção de H2 – (PAH + CdSe)/(PEDOT:PSS + TiO2 STS-100) – foi otimizado em 120 camadas. Na avaliação da contribuição do tipo de nanopartícula do semicondutor para a geração de H2, os resultados de cromatografia indicaram que a combinação de (CdSe + TiO2 STS-100) promove um aumento de 75% desta geração quando comparado ao FFA composto somente pelo semicondutor TiO2 STS-100.
Keywords: Filmes finos; Semicondutores; Hidrogênio; Polímeros; Thin films; Semiconductors; Hydrogen; Polymers